Chinese Innovation Research to Industrial Transformation and Upgrading: Processing innovation in case company - Hu, Chenjuan (My University, 2016)
China was famous as world factory. Most small and medial size Chinese industry are facing the industrial transformation and upgrading stage. Innovation level as a competitive competence is extremely important to manufacturing. However, sophisticated technique and radical innovation skills are still blank in level of SMEs. The thesis will focus on solve innovation dilemma in SMEs, that Chinese SMEs prefer incremental innovation rather than radical innovation, and radical innovation cannot occur in large scale. There are some barriers that impeded Chinese innovation had also been discussed. To clarify the barriers helps industry easier innovate than before. Research will combine both quantitative data analysis and qualitative data analysis to explore three questions. Quantitative data observed from case company. By using statistical method, correlation between data can be recognized. Qualitative data received mainly from a talk interview. This interview organized by Chinese official television station. Business network relationship reports and journals are the second main resources for qualitative data analysis. The thesis will indicate that Chinese SMEs prefer slow innovation has historical reason and quick profit desire. Number of innovation might have no different between big companies and small companies, but big companies have more resources to do radical innovation than small ones. All action bonds within business value net are somehow affect innovation development in China. A efficient collaborative networks with each action bonds can help to increase the innovation level.
Keywords: Innovation; Business network management; Process efficiency; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|